High-strength composite glass and processing technology thereof

By using specific proportions of materials and high-temperature calcining and hot-pressing molding processes, composite glass with excellent high strength, wear resistance and heat insulation performance is prepared, which solves the shortcomings of existing composite glasses in toughness, wear resistance and heat insulation performance.

CN119661119AInactive Publication Date: 2025-03-21SHANDONG MEIXIN GLASS TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411889224.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-03-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing high-strength composite glass still lacks toughness and wear resistance, and the lack of heat insulation components during its preparation leads to insufficient heat insulation performance.

Method used

High-strength composite glass is prepared by high-temperature calcination and hot-press molding processes such as 45-65% silica, 5-10% alumina, 5-10% calcium carbonate, 3-5% barium oxide, 2-3% zirconia, 6-8% high-temperature resistant modified bisphenol A-type epoxy resin, 6-8% E-type glass fiber, 1-1.5% isocyanate, 2-5% magnesium hydroxide, 1-1.5% polyether amide, 1.5-3% tert-butylquinone and 1-1.5% hydroxystyrene.

Benefits of technology

It realizes high-strength, high wear resistance and high toughness composite glass, which can effectively block heat conduction, reduce energy consumption, and filter most harmful ultraviolet rays to protect indoor items.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of composite glass, and particularly relates to high-strength composite glass and a processing technology thereof. The invention relates to high-strength composite glass, which is prepared from the following materials in percentage by weight: 45 to 65 percent of silicon dioxide, 5 to 10 percent of aluminum oxide, 5 to 10 percent of calcium carbonate, 3 to 5 percent of barium oxide, 2 to 3 percent of zirconium oxide, 6 to 8 percent of high-temperature-resistant modified bisphenol A epoxy resin, 6 to 8 percent of E type glass fiber, 1 to 1.5 percent of isocyanate, 2 to 5 percent of magnesium hydroxide, 1 to 1.5 percent of polyether amide, 1.5 to 3 percent of tert-butyl quinone and 1 to 1.5 percent of hydroxystyrene. The glass has high strength and impact resistance, the glass cannot be broken into sharp fragments when the glass is impacted, threats to personal safety are reduced, heat conduction can be effectively blocked, and the service life of the glass is prolonged. Meanwhile, most of harmful ultraviolet rays can be filtered out, indoor furniture, floors and artworks are protected, and color fading and damage are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite glass, and in particular relates to a high-strength composite glass and a processing technology thereof. Background Art

[0002] The development of glass can be traced back thousands of years. The earliest glass products appeared around 3500 BC and were mainly used for decorations and simple containers. In 1000 BC, more complex glass manufacturing techniques such as blowing and mold forming began to appear in Egypt and Mesopotamia. In the Middle Ages, glass craftsmanship in Venice and other places reached its peak, and high-end products such as stained glass and mirrors appeared. The Industrial Revolution in the 19th century promoted the mechanization of glass manufacturing, promoted large-scale production and the emergence of new types of glass (such as tempered glass and laminated glass). Today, with the advancement of science and technology, the functionalization of glass has developed rapidly and is widely used in construction, automobiles, electronics and other fields, meeting higher demands for safety, heat insulation and aesthetics.

[0003] As the construction and automobile industries attach importance to safety, composite glass has gradually become popular due to its impact resistance and anti-fragmentation properties. Composite glass usually has better sound insulation and heat insulation performance, which meets the requirements of modern buildings for comfort and energy efficiency. A Chinese patent with publication number CN108314328A discloses a method for preparing high-strength composite glass, which uses silicon-modified glass to obtain relatively good strength, but its process is relatively simple, and the prepared glass still has deficiencies in toughness and wear resistance. At the same time, no heat insulation component is added during its preparation process, resulting in insufficient heat insulation performance of the prepared glass.

[0004] In view of the above technical defects, a solution is now proposed. Summary of the invention

[0005] The purpose of the present invention is to provide a high-strength composite glass and a processing technology thereof, which has the characteristics of high strength, high wear resistance and high toughness.

[0006] To achieve the above object, the present invention adopts the following technical scheme: a high-strength composite glass is composed of the following percentage materials: 45-65% silicon dioxide, 5-10% aluminum oxide, 5-10% calcium carbonate, 3-5% barium oxide, 2-3% zirconium oxide, 6-8% high temperature resistant modified bisphenol A type epoxy resin, 6-8% E-type glass fiber, 1-1.5% isocyanate, 2-5% magnesium hydroxide, 1-1.5% polyether amide, 1.5-3% tert-butylquinone and 1-1.5% hydroxystyrene; Furthermore, the preparation method of the high temperature resistant modified bisphenol A epoxy resin comprises the following steps: A1: Add bisphenol A epoxy resin and glacial acetic acid into deionized water, heat in an oil bath pot equipped with a thermometer and a magnetic stirrer, stir and react for 30 minutes at a temperature of 110-150°C and a stirring rate of 800-1000 rpm. After complete dissolution, adjust the temperature to 45-60°C, set the stirring rate to 300-400 rpm, and stir for 1.5 hours to obtain intermediate A; A2: Aluminum silicate and silicon nitride are added to the intermediate A, and a flask equipped with a stirrer and a thermometer is used. The flask mouth is tilted at 45 degrees and the bottom is heated with an alcohol lamp. The reaction is stirred for 30 minutes at a temperature of 30-45°C and a stirring rate of 400-600rpm. Then, a serpentine tube and condensed water are used to heat the product for reflux. The reflux reaction is carried out for 5-6 hours. After the reaction is completed, the reaction product is cooled to room temperature and then vacuum filtered. The filter cake is washed with deionized water for 3-5 times, and then placed in a vacuum drying oven and dried at a temperature of 80-85°C for 3-5 hours to obtain the intermediate B; A3: Transfer intermediate B to a distillation tower, and collect the distillation bottom product after distillation for 3-5 hours; transfer the distillation bottom product to room temperature and cool for 1-2 hours to obtain intermediate C, then add stearylamide to intermediate C and transfer it to a mixer, set the mixer speed to 1200-1500 rpm, and stir for 30 minutes to obtain intermediate D; A4: The intermediate D is transferred to a degassing machine and vacuum degassing is performed for 1.5 hours to obtain a high temperature resistant modified bisphenol A epoxy resin.

[0007] Furthermore, the concentration of glacial acetic acid in step A1 is 9%; the mass ratio of bisphenol A epoxy resin, glacial acetic acid and deionized water is 5:1:10; the mass ratio of intermediate A, aluminum silicate and silicon nitride in step A2 is 5:1:1; and the mass ratio of intermediate C and stearamide in step A3 is 50:1.

[0008] A processing technology for high-strength composite glass comprises the following steps: S1: Grind silicon dioxide, aluminum oxide, calcium carbonate, barium oxide and zirconium oxide in a grinder for 15-30 minutes. After grinding, mix the powders evenly and pass through an 800-mesh metal sieve to form a mixed powder; S2: placing the mixed powder in a high temperature reaction furnace, heating it to 1580-1640°C, and calcining it at high temperature for 1-2 hours to obtain glass liquid; S3: pouring the glass liquid into water, cooling and solidifying it into glass blocks and glass particles, mixing the glass blocks and glass particles, grinding them in a grinder for 15-30 minutes, and then passing through an 800-mesh metal sieve to obtain glass powder; S4: placing high temperature resistant modified bisphenol A epoxy resin, E-type glass fiber and magnesium hydroxide in a high temperature reactor, heating to 65-80°C, using a stirrer to accelerate dissolution, adjusting the stirrer speed to 300-500rpm, stirring and dissolving at high temperature for 1-1.5h, and adding isocyanate, polyether amide, tert-butyl quinone and hydroxystyrene after observing that the materials in the reactor are completely dissolved, adjusting the temperature to 45-60°C and the stirrer speed to 200-350rpm, stirring and reacting for 30min to obtain a composite glass additive; S5: Add glass powder to the composite glass additive, heat to 95-110°C, continue stirring and react for 0.5-1h, cool to 25°C after the reaction is completed, transfer the product to a vacuum degassing machine after cooling, and vacuum degas for 0.5-1h; S6: pouring the degassed product into a mold for hot pressing, adjusting the hot pressing temperature to 120-150° C., the molding pressure to 60-80 KPa, and hot pressing for 4-5 hours to obtain a high-strength composite glass.

[0009] Furthermore, the silicon dioxide is a hydrophilic silicon dioxide powder with a specification of 500 mesh; the zirconium oxide is a hydrophilic zirconium oxide powder with a particle size of 30 nm.

[0010] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are that the present invention has high strength and impact resistance, the glass will not break into sharp fragments when impacted, reducing the threat to personal safety, and the present invention can effectively block the conduction of heat, reduce the energy consumption of air conditioning and heating, thereby improving the energy efficiency of buildings and reducing energy costs. At the same time, the present invention can filter out most of the harmful ultraviolet rays, protect indoor furniture, floors and artworks, and reduce fading and damage. DETAILED DESCRIPTION

[0011] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments.

[0012] The experimental methods in the following examples, unless otherwise specified, are conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials and reagents used in the following examples, unless otherwise specified, can be obtained from commercial channels.

[0013] Example 1 Furthermore, the concentration of glacial acetic acid in step A1 is 9%; the mass ratio of bisphenol A epoxy resin, glacial acetic acid and deionized water is 5:1:10; and the mass ratio of intermediate A, aluminum silicate and silicon nitride in step A2 is 5:1:1.

[0014] 1: Add 100g of bisphenol A epoxy resin and 20ml of 9% glacial acetic acid into 200ml of deionized water, heat in an oil bath pot equipped with a thermometer and a magnetic stirrer, stir and react for 30min at a temperature of 150°C and a stirring rate of 1000rpm. After complete dissolution, adjust the temperature to 60°C, set the stirring rate to 400rpm, and stir for 1.5h to obtain intermediate A; 2: Add 40g of aluminum silicate and 40g of silicon nitride to 200ml of intermediate A, use a flask equipped with a stirrer and a thermometer, tilt the flask mouth at 45°, heat the bottom with an alcohol lamp, stir and react for 30min at a temperature of 45°C and a stirring rate of 600rpm, then use a serpentine tube and condensed water to reflux the product, reflux for 6h, cool the reaction product to room temperature after the reaction, then vacuum filter, wash the filter cake with deionized water 5 times, then place it in a vacuum drying oven, and dry it at 85°C for 5h to obtain intermediate B; 3: Transfer intermediate B to a distillation tower, collect the bottom product after distillation for 5 hours; transfer the bottom product to room temperature and cool for 2 hours to obtain 200 ml of intermediate C, then add 4 g of stearamide to intermediate C and transfer to a mixer, set the mixer speed to 1500 rpm. Stir for 30 minutes to obtain 145 g of intermediate D; 4: The intermediate D was transferred to a degassing machine and vacuum degassing was performed for 1.5 hours to obtain 112 g of Example 1.

[0015] Table 1, reagent parameters used in Example 1 Drug Name source model parameter Bisphenol A epoxy resin Langfang Senqiang Environmental Protection Technology Co., Ltd. E-44 1kg glacial acetic acid Shandong Baijing New Materials Co., Ltd. 7452 25kg Aluminum silicate Shijiazhuang Mingtai New Materials Co., Ltd. GSLF 1kg Silicon Nitride Anhui Nanhao Electronic Technology Co., Ltd. KR-Si3N4 99.9% Stearamide Jiangxi Zhilian New Materials Co., Ltd. 124-26-5 1kg Example 2 1: Add bisphenol A epoxy resin and glacial acetic acid into deionized water, heat in an oil bath pot equipped with a thermometer and a magnetic stirrer, stir and react for 30 minutes at a temperature of 110-150°C and a stirring rate of 800-1000 rpm. After complete dissolution, adjust the temperature to 45-60°C, set the stirring rate to 300-400 rpm, and stir for 1.5 hours to obtain intermediate A; 2: Add aluminum silicate and silicon nitride to intermediate A, use a flask equipped with a stirrer and a thermometer, tilt the flask mouth at 45° and heat the bottom with an alcohol lamp, stir and react for 30 minutes at a temperature of 30-45°C and a stirring rate of 400-600rpm, then use a serpentine tube and condensed water to heat and reflux the product, heat and reflux for 5-6 hours, and after the reaction is completed, cool the reaction product to room temperature, then vacuum filter, wash the filter cake with deionized water for 3-5 times, and then place it in a vacuum drying oven and dry it at a temperature of 80-85°C for 3-5 hours to obtain intermediate B; 3: Transfer intermediate B to a distillation tower, and collect the distillation bottom product after distillation for 3-5 hours; transfer the distillation bottom product to room temperature and cool for 1-2 hours to obtain intermediate C, then add stearylamide to intermediate C and transfer it to a mixer, set the mixer speed to 1200-1500 rpm, and stir for 30 minutes to obtain intermediate D; 4: Transfer intermediate D to a degassing machine and perform vacuum degassing for 1.5 hours to obtain a high temperature resistant modified bisphenol A epoxy resin.

[0016] Table 2, reagent parameters used in Example 2 Drug Name source model parameter Bisphenol A epoxy resin Langfang Senqiang Environmental Protection Technology Co., Ltd. E-44 1kg glacial acetic acid Shandong Baijing New Materials Co., Ltd. 7452 25kg Aluminum silicate Shijiazhuang Mingtai New Materials Co., Ltd. GSLF 1kg Silicon Nitride Anhui Nanhao Electronic Technology Co., Ltd. KR-Si3N4 99.9% Stearamide Jiangxi Zhilian New Materials Co., Ltd. 124-26-5 1kg Example 3 1: Place 130g of silicon dioxide, 10g of aluminum oxide, 10g of calcium carbonate, 6g of barium oxide, and 4g of zirconium oxide in a grinder and grind for 30 minutes. After grinding, mix the powders evenly and pass through an 800-mesh metal sieve to form a mixed powder; 2: Place the mixed powder in a high-temperature reaction furnace, heat it to 1640°C, and calcine it at high temperature for 2 hours to obtain glass liquid; 3: Pour the glass liquid into water and let it cool and solidify into glass blocks and glass particles. Mix the glass blocks and glass particles and grind them in a grinder for 30 minutes. Then pass through an 800-mesh metal sieve to obtain 150g of glass powder. 4: 12g of Example 1, 12g of E-type glass fiber and 4g of magnesium hydroxide were placed in a high-temperature reactor, the temperature was raised to 80°C, a stirrer was used to accelerate the dissolution, the stirrer speed was adjusted to 500rpm, the high-temperature stirring and dissolving was performed for 1.5h, and after the materials in the reactor were observed to be completely dissolved, 2ml of isocyanate, 2ml of polyetheramide, 3ml of tert-butylquinone and 2ml of hydroxystyrene were added, the temperature was adjusted to 60°C, the stirrer speed was adjusted to 350rpm, and the stirring reaction was performed for 30min to obtain 32ml of composite glass additive; 5: Add 150g of glass powder to the composite glass additive, heat to 110°C, continue stirring and react for 1h, cool to 25°C after the reaction is completed, transfer the product to a vacuum degassing machine after cooling, and vacuum degas for 1h; 6: Pour the degassed product into a mold for hot pressing. Adjust the hot pressing temperature to 150°C and the molding pressure to 80 KPa. Hot press for 5 hours to obtain 180 g of Example 3.

[0017] Table 3, reagent parameters used in Example 3 Drug Name source model parameter Silicon dioxide Guangzhou Zedanlu New Materials Co., Ltd. ZDL-500 500 mesh Alumina Dongguan Dongchao New Material Technology Co., Ltd. DCA-S 25kg Calcium carbonate Lingshou County Jianhui Mineral Products Processing Factory JH-02 500 mesh Barium Oxide Aladdin B104890 25g Zirconia Hangzhou Jiupeng New Materials Co., Ltd. CY-R10 1kg E-type fiberglass Qingdao Yilitong Composite Materials Co., Ltd. YLT-30 15·3 Magnesium hydroxide Hebei Songzhi Chemical Technology Co., Ltd. 068 20kg Isocyanate Shandong Rongwei Chemical Co., Ltd. MDI 2kg Polyetheramide Guangdong Zhongke Hongtai New Materials Co., Ltd. K-218 1kg Tert-Butylquinone Aladdin B102514 25g Hydroxystyrene Wuhan Lanabai Pharmaceutical Chemical Co., Ltd. P20230316 100g Example 4 45-65% silicon dioxide, 5-10% aluminum oxide, 5-10% calcium carbonate, 3-5% barium oxide, 2-3% zirconium oxide, 6-8% high temperature resistant modified bisphenol A type epoxy resin, 6-8% E-type glass fiber, 1-1.5% isocyanate, 2-5% magnesium hydroxide, 1-1.5% polyether amide, 1.5-3% tert-butyl quinone and 1-1.5% hydroxystyrene; 1: Place 90g of silicon dioxide, 20g of aluminum oxide, 20g of calcium carbonate, 10g of barium oxide, and 6g of zirconium oxide in a grinder and grind for 30 minutes. After grinding, mix the powders evenly and pass through an 800-mesh metal sieve to form a mixed powder; 2: Place the mixed powder in a high-temperature reaction furnace, heat it to 1600°C, and calcine it at high temperature for 2 hours to obtain glass liquid; 3: Pour the glass liquid into water and let it cool and solidify into glass blocks and glass particles. Mix the glass blocks and glass particles and grind them in a grinder for 30 minutes. Then pass through an 800-mesh metal sieve to obtain 130g of glass powder. 4: 16g of Example 2, 16g of E-type glass fiber and 10g of magnesium hydroxide were placed in a high-temperature reactor, the temperature was raised to 80°C, a stirrer was used to accelerate the dissolution, the stirrer speed was adjusted to 500rpm, the high-temperature stirring and dissolving was performed for 1.5h, and after the materials in the reactor were observed to be completely dissolved, 3g of isocyanate, 3g of polyetheramide, 6g of tert-butylquinone and 3g of hydroxystyrene were added, the temperature was adjusted to 60°C, the stirrer speed was adjusted to 200rpm, and the reaction was stirred for 30min to obtain a composite glass additive; 5: Add 130g of glass powder to the composite glass additive, heat to 110°C, continue stirring and react for 1h, cool to 25°C after the reaction is completed, transfer the product to a vacuum degassing machine after cooling, and vacuum degas for 1h; 6: Pour the degassed product into a mold for hot pressing. Adjust the hot pressing temperature to 150°C and the molding pressure to 80 KPa. Hot press for 4 hours to obtain 184 g of Example 4.

[0018] Table 4, reagent parameters used in Example 4 Drug Name source model parameter Silicon dioxide Guangzhou Zedanlu New Materials Co., Ltd. ZDL-500 500 mesh Alumina Dongguan Dongchao New Material Technology Co., Ltd. DCA-S 25kg Calcium carbonate Lingshou County Jianhui Mineral Products Processing Factory JH-02 500 mesh Barium Oxide Aladdin B104890 25g Zirconia Hangzhou Jiupeng New Materials Co., Ltd. CY-R10 1kg E-type fiberglass Qingdao Yilitong Composite Materials Co., Ltd. YLT-30 15·3 Magnesium hydroxide Hebei Songzhi Chemical Technology Co., Ltd. 068 20kg Isocyanate Shandong Rongwei Chemical Co., Ltd. MDI 2kg Polyetheramide Guangdong Zhongke Hongtai New Materials Co., Ltd. K-218 1kg Tert-Butylquinone Aladdin B102514 25g Hydroxystyrene Wuhan Lanabai Pharmaceutical Chemical Co., Ltd. P20230316 100g Comparative Example 1 Example 1 of Chinese patent publication number CN108314328A was selected as comparative example 1.

[0019] Comparative Example 2 Example 1 of the Chinese patent with publication number CN108483903A was selected as comparative example 2.

[0020] Performance Testing: According to the "Glass Hardness Test Method" specified in GB / T 9341-2000, hardness tests were performed on Example 3, Example 4, Comparative Example 1 and Comparative Example 2; According to the "Glass Abrasion Resistance Test Method" specified in GB / T 1863-2008, the abrasion resistance test was performed on Example 3, Example 4, Comparative Example 1 and Comparative Example 2; According to the "Test Methods for Physical Properties of Glass for Architectural Use Part 1: Determination of Bending Strength" specified in GB / T 9966.1-2014, bending strength tests were performed on Example 3, Example 4, Comparative Example 1 and Comparative Example 2; According to the "Test Methods for Physical Properties of Glass for Architectural Use Part 12: Determination of Impact Resistance" specified in GB / T 9966.12-2014, the impact resistance of Example 3, Example 4, Comparative Example 1 and Comparative Example 2 was tested.

[0021] Table 5, Physical properties test of Example 3, Example 4, Comparative Example 1 and Comparative Example 2 Group Shore hardness (D) Wear reduction Bending strength (MPa) Impact strength (MPa) Example 3 144 0.7% 258 373 Example 4 152 0.6% 261 381 Comparative Example 1 125 1.2% 237 362 Comparative Example 2 121 1.3% 229 357 By analyzing Table 5, it can be seen that compared with Comparative Examples 1 and 2, the composite glass prepared by the present invention has better wear resistance, impact resistance and toughness, and can be suitable for different usage scenarios and different usage environments.

[0022] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A high-strength composite glass, characterized in that: The composition is composed of the following percentage materials: 45-65% silicon dioxide, 5-10% aluminum oxide, 5-10% calcium carbonate, 3-5% barium oxide, 2-3% zirconium oxide, 6-8% high temperature resistant modified bisphenol A type epoxy resin, 6-8% E-type glass fiber, 1-1.5% isocyanate, 2-5% magnesium hydroxide, 1-1.5% polyether amide, 1.5-3% tert-butyl quinone and 1-1.5% hydroxystyrene; The preparation method of the high temperature resistant modified bisphenol A epoxy resin comprises the following steps: A1: Add bisphenol A epoxy resin and glacial acetic acid into deionized water, heat in an oil bath pot equipped with a thermometer and a magnetic stirrer, stir and react for 30 minutes at a temperature of 110-150°C and a stirring rate of 800-1000 rpm. After complete dissolution, adjust the temperature to 45-60°C, set the stirring rate to 300-400 rpm, and stir for 1.5 hours to obtain intermediate A; A2: Aluminum silicate and silicon nitride are added to the intermediate A, and a flask equipped with a stirrer and a thermometer is used. The flask mouth is tilted at 45 degrees and the bottom is heated with an alcohol lamp. The reaction is stirred for 30 minutes at a temperature of 30-45°C and a stirring rate of 400-600rpm. Then, a serpentine tube and condensed water are used to heat the product for reflux. The reflux reaction is carried out for 5-6 hours. After the reaction is completed, the reaction product is cooled to room temperature and then vacuum filtered. The filter cake is washed with deionized water for 3-5 times, and then placed in a vacuum drying oven and dried at a temperature of 80-85°C for 3-5 hours to obtain the intermediate B; A3: Transfer intermediate B to a distillation tower, and collect the distillation bottom product after distillation for 3-5 hours; transfer the distillation bottom product to room temperature and cool for 1-2 hours to obtain intermediate C, then add stearylamide to intermediate C and transfer it to a mixer, set the mixer speed to 1200-1500 rpm, and stir for 30 minutes to obtain intermediate D; A4: The intermediate D is transferred to a degassing machine and vacuum degassing is performed for 1.5 hours to obtain a high temperature resistant modified bisphenol A epoxy resin.

2. The high-strength composite glass according to claim 1, characterized in that: The concentration of glacial acetic acid in step A1 is 9%; the mass ratio of bisphenol A epoxy resin, glacial acetic acid and deionized water is 5:1:

10.

3. The high-strength composite glass according to claim 1, characterized in that: The mass ratio of the intermediate A, aluminum silicate and silicon nitride in the step A2 is 5:1:

1.

4. The high-strength composite glass according to claim 1, characterized in that: The mass ratio of intermediate C to stearamide in step A3 is 50:

1.

5. The high-strength composite glass according to claim 1, characterized in that: The silicon dioxide is hydrophilic silicon dioxide powder with a specification of 500 meshes.

6. The high-strength composite glass according to claim 1, characterized in that: The zirconium oxide is a hydrophilic zirconium oxide powder with a particle size of 30 nm.

7. The processing technology of high-strength composite glass according to claim 1, characterized in that: The following steps are involved: S1: Grind silicon dioxide, aluminum oxide, calcium carbonate, barium oxide and zirconium oxide in a grinder for 15-30 minutes. After grinding, mix the powders evenly and pass through an 800-mesh metal sieve to form a mixed powder; S2: placing the mixed powder in a high temperature reaction furnace, heating it to 1580-1640°C, and calcining it at high temperature for 1-2 hours to obtain glass liquid; S3: pouring the glass liquid into water, cooling and solidifying it into glass blocks and glass particles, mixing the glass blocks and glass particles, grinding them in a grinder for 15-30 minutes, and then passing through an 800-mesh metal sieve to obtain glass powder; S4: placing high temperature resistant modified bisphenol A epoxy resin, E-type glass fiber and magnesium hydroxide in a high temperature reactor, heating to 65-80°C, using a stirrer to accelerate dissolution, adjusting the stirrer speed to 300-500rpm, stirring and dissolving at high temperature for 1-1.5h, and adding isocyanate, polyether amide, tert-butyl quinone and hydroxystyrene after observing that the materials in the reactor are completely dissolved, adjusting the temperature to 45-60°C and the stirrer speed to 200-350rpm, stirring and reacting for 30min to obtain a composite glass additive; S5: Add glass powder to the composite glass additive, heat to 95-110°C, continue stirring and react for 0.5-1h, cool to 25°C after the reaction is completed, transfer the product to a vacuum degassing machine after cooling, and vacuum degas for 0.5-1h; S6: pouring the degassed product into a mold for hot pressing, adjusting the hot pressing temperature to 120-150° C., the molding pressure to 60-80 KPa, and hot pressing for 4-5 hours to obtain a high-strength composite glass.

Citation Information

Patent Citations

  • Preparation method of high-strength compound glass

    CN108314328A

  • Fluorescent composite glass and preparation method thereof

    CN108483903A

  • Flame retardant hot set epoxy resin composition

    CN101054460A

  • Resin matrix glass fiber reinforced plastic and preparation method thereof

    CN118956100A

  • Fireproof high-temperature-resistant glass

    CN217472606U